2020
DOI: 10.1186/s41938-020-00299-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neem leaves as soil amendment for the control of collar rot disease of chickpea

Abstract: Chickpea (Cicer arietinum L.) is an important grain legume that is attacked by the fungal pathogen, Sclerotium rolfsii, responsible for collar rot disease. In the present study, the pathogen was isolated from diseased chickpea seedlings and identified on molecular basis using internal transcribed spacer (ITS) and β-tubulin markers. To control this pathogen, an in vivo study was carried out, using Neem (Azadirachta indica A. Juss.) leaf dry biomass (1, 2, and 3%) as soil amendment. A broad-spectrum fungicide ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This fungicide was also highly effective against C. lunata and P. expansum causing and 69-90% reduction in their in vitro growth due to a concentration range of 50 to 250 ppm (Butt et al, 2020;Hassan et al, 2020). Khan et al (2020) reported that mencozeb significantly reduced the incidence of collar rot disease caused by S. rolfsii. Similarly, Türkölmez and Dervis (2017) reported significant control of fungal diseases of apricot and cherry caused by Phytophthora palmivora, due to application metalaxyl+mencozeb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fungicide was also highly effective against C. lunata and P. expansum causing and 69-90% reduction in their in vitro growth due to a concentration range of 50 to 250 ppm (Butt et al, 2020;Hassan et al, 2020). Khan et al (2020) reported that mencozeb significantly reduced the incidence of collar rot disease caused by S. rolfsii. Similarly, Türkölmez and Dervis (2017) reported significant control of fungal diseases of apricot and cherry caused by Phytophthora palmivora, due to application metalaxyl+mencozeb.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the complete eradication of this devastating pathogen is very critical (Atri and Kaur, 2021). Different integrated management strategies such as cultural and biological control have been investigated before including chemical practices (Ali et al, 2020;Khan et al, 2020). The application of synthetic chemicals in agriculture is a common practice for the effective control of plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…After one‐week of pathogen inoculation, the pot soil was amended with C. quinoa whole plant dry biomass at different concentrations viz. 1%, 2% and 3% (wt/wt) except soil of the negative and the positive control treatments, and watered to leach down the allelochemicals from the added plant material (Khan et al, 2020). Five treatment viz.…”
Section: Methodsmentioning
confidence: 99%
“…S. rolfsii is a devastating soil borne fungal pathogen that causes diseases in more than 500 plant species including chickpea, chili, bell pepper, etc. (Javaid et al 2020;Khan et al 2020;Jabeen et al 2021). The continuous use of synthetic fungicides can cause various problems to plant animals and soils because these fungicides are difficult to degrade naturally (Dharmaputra et al 2016).…”
Section: Introductionmentioning
confidence: 99%